The decline of the Fossil Age is the rise of distributive justice - J. Daniel Dahm; Stephan Bannas (Revue Internationale de Politique de Développement)
The many cultures of the world today face a huge challenge: the organisation of a sustainable and just society, which enables people to have a share in the essentials of life, in knowledge and political and cultural development, as well as access to and the use of technological infrastructure. Sustainable development demands more than simply maintaining and protecting the climatic and ecological balance of the bio-geosphere; it requires a constructive effort to enable and promote the evolution of living things and the cooperative development of the diversity of the Earth’s cultural forms as a complement to bio-ecological evolution. In the co-evolution of humanity, economics has taken on an increasingly significant interface function with relation to nature. Economics mediates between the ideas, needs and demands of human culture and social reality on the one hand, and natural resources on the other. The role of energy availability has become ever more important as a result of industrialisation and the increasing tendency to use material and technological methods for economic production. Energy became the means and the motor of economic development. Its availability and access to it increased in significance for the development of industry, wealth and the creation of infrastructure. Many alternative cultural forms had already been marginalised and consigned to history, and many geographical areas had already been restructured to become suppliers of resources for transport to the booming western European-style societies. Together with an increasing shift in the orientation of models of prosperity from “being” to “having” (cp. Fromm, 1976) and the expansion of the consumer goods industry necessary for this, energy availability and energy use became entrenched as a prerequisite for prosperity. Energy transformed ideas and wishes into material goods and legitimised the conception that everything was endlessly feasible. At the start of the 21st century, energy is the source, the prerequisite and the legitimation of the model of power and consumption of the last century. However, there is neither the material basis nor the energy availability for us to pursue further, and around the globe, the resource-hungry and energy-hungry lifestyle of the past decades. This lifestyle never brought happiness (cp. Kasser, 2002). It could never be achieved throughout the world. Today, energy no longer embodies the genie from the bottle, who works wonders, but rather a model for limitless economic growth, material excess and the accumulation of economic, social and political power by one group at the expense of the others. Energy is frequently seen as being synonymous with the climatic and ecological crisis, with greenhouse gases, global injustice and military conflicts. At the same time, though, energy today once again represents hope. The age of renewable energy has dawned and, with its potential for decentralised production, its polycentric supply infrastructure and ecological balance, it represents a new technological age. Renewable energy gives new strength to ideas of good governance, of justice, participation and stewardship of our social goods.